ADAM FRANTIŠEK KOLLÁR – PIONEER OF TERESIAN ENLIGHTENMENT, SCHOOL REFORMER - GEJDOŠ, Miroslav (HUMANITARIAN STUDIES: HISTORY AND PEDAGOGY, 2022)
In this article, the author introduces the important personality of Adam František Kollár, who is one of the most prominent personalities of science in the 18th century. Adam Franciszek Kollar is considered one of the pioneers of the Theresian Enlightenment. He excelled as a librarian, historian, school reformer and ethnologist. He was called the "Slovak Socrates". His views on humanity and his striving for equal rights for all Hungarians also attract attention. Adam František Kollár was one of the most important Slovak personalities of the philosophical, pedagogical and social life of the 18th century. He contributed to the development of Old Slavic historiography, was a pioneer of modern Slavic studies and created the organizational foundations of Hungarian science, which also had an impact on Slovakia. Already during his lifetime he was considered a scholar known throughout Europe. He had a political influence on the policy of the Hungarian court. Kollár took up the property dispute between the Esterházy family and the Viennese court and won it. In uncovering the conception of his personality, we have focused on the historical development of the issue, using direct, analytical and comparative methods. We also used literary-historical and factual methods. In the context of pedagogical historiography, it is necessary to mention, first of all, the time in which Adam František Kollár lived, the situation and his pedagogical views, which he found and gradually developed during his life. Therefore, in our study we have relied on the opinions of authors who dealt with the above mentioned topic, especially Elias, Hamada, Tybensky, Wurtzbach, on their researches and approaches to the search for the meaning of existence and life in the 18th century. This has made it possible to focus on explaining the main pedagogical and philosophical views present in the works of the eminent Slovak thinker and reflecting the life of Adam František Kollár. The contribution of his pedagogical works lies in his progressive (for that time) views in the field of education and training. In his works, he strives to ensure equality in education and to teach subjects for the practical needs of pupils based on the environment in which they grow up. It can be assumed that A. F. Kollár, as an expert in several foreign oriental languages, will try to promote their teaching. But, on the contrary, in his writings on teacher education he emphasizes the teaching of the mother tongue, and knowledge of other languages should be used only for the improvement and refinement of one's own language.